Hearing process in children with cleft lip and palate with or without history of otitis - de Moraes, Tamyne Ferreira Duarte; Salvador, Karina Krähembühl; Cruz, Mariana Sodário; Campos, Carolina Ferreira; Feniman, Mariza Ribeiro (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Considering that hearing loss and otologic complications can interfere in the maturation process of central nervous system, this study aimed to check the performance of children with cleft lip and palate with or without the history of otitis media in the evaluation of the hearing process.Method: Prospective study. Were evaluated 20 children with operated cleft lip and palate, aged between 7 to 10 years old, divided into group I - 10 children with cleft lip and palate with history of otitis - and group II - with 10 children with cleft lip and palate with no history of otitis. Were performed diotic, monotic and dichotic tests.Results: All the children presented a bad performance in at least one dichotic test. In these diotic tests, children of group I had the worst performance, while in the monotic tests the worst performance was of group II.Conclusion: All the children with history of otitis and all the children with no history have presented a bad performance in the processing tests,in other words, some kind of central alteration was found in 100% of the children studied in both groups.
Keywords: hearing; cleft lip; cleft palate; otitis media